Predictive Value of Two-Dimensional Speckle-Tracking Echocardiography in Patients Undergoing Surgical Ventricular Restoration - Nemchyna, Olena; Solowjowa, Natalia; Dandel, Michael; Hrytsyna, Yuriy; Stein, Julia; Knierim, Jan; Schoenrath, Felix; Hennig, Felix; Falk, Volkmar; Knosalla, Christoph (Frontiers in Cardiovascular Medicine, 2022)
Objectives Parameters of left ventricular (LV) mechanics, obtained from speckle-tracking echocardiography (STE), were found to be of prognostic value in patients with heart failure and those who underwent cardiac surgery. This study aimed to assess the value of STE in patients scheduled to undergo surgical ventricular restoration (SVR). Methods A total of 158 consecutive patients with baseline STE who underwent SVR due to an LV anteroapical aneurysm were included in the analysis. Preoperative longitudinal STE parameters were evaluated for their association with an outcome, defined as all-cause mortality, LV assist device implantation, or heart transplantation. The echocardiographic follow-up to assess the change in the regional function of the segments remote from the aneurysm was performed in 43 patients at a median of 10 months [interquartile range (IQR): 6–12.7 months] after SVR. Results During a median follow-up of 5.1 years (IQR: 1.6–8.7 years), events occurred in 68 patients (48%). Less impaired mean basal end-systolic longitudinal strain (BLS) with a cutoff value ≤ −10.1 % demonstrated a strong association with event-free survival, also in patients with an LV shape corresponding to an intermediate shape between aneurysmal and globally akinetic. Initially hypo- or akinetic basal segments with preoperative end-systolic strain ≤ −7.8% showed a greater improvement in wall motion at the short-term follow up. Conclusion Patients with less impaired preoperative BLS exhibited a better event-free survival after SVR, also those with severe LV remodeling. The preserved preoperative segmental longitudinal strain was associated with a greater improvement in regional wall motion after SVR. BLS assessment may play a predictive role in patients with an LV anteroapical aneurysm who are scheduled to undergo SVR.